Learning process, accumulation of knowledge and innovation systems: the coevolution of physical and social technologies as source of economic development - Pereira, Adriano José (2012)
By conceiving the firm as an institution of production and learning, the “institutionalistevolutionary” approach has been making progress in understanding the causes and effects of its performance as an agent of innovation. From this perspective, this article is a survey of the theoretical discussion about the role of companies in the consolidation of innovation systems, emphasizing the importance of the learning process as a basis for the knowledge accumulation necessary to promote technological, organizational and also institutional innovations. In this sense, the paper shows that companies contribute and, at the same time, benefit from innovation systems, as the learning process is an inherent part of the “co-evolution of physical and social technologies”, providing advances in micro and meso economic levels, thus promoting economic development.